Brucella melitensis endocarditis: successful treatment of an infected prosthetic mitral valve - O'Meara, J. B. (1974)
O'Meara, J. B., Eykyn, Susannah, Jenkins, B. S., Braimbridge, M. V., and Phillips, I. (1974).Thorax, 29, 377-381. Brucella melitensis endocarditis: successful treatment of an infected prosthetic mitral valve. A 38-year-old man had a mitral valve replacement for rheumatic calcific mitral stenosis and regurgitation; following this operation he remained well for 10 months. He then presented with cough, abdominal pain, and rigors, and Brucella melitensis type 3 was repeatedly isolated from blood cultures. His clinical condition deteriorated rapidly and an emergency valve replacement was performed. He was then treated with co-trimoxazole for 12 months and made an excellent recovery. This is the first reported case of brucella endocarditis arising de novo on a prosthetic heart valve.